The effect of vitamin D supplementation on bone formation around titanium implants in diabetic rats - Ali Akhavan; Zahra Noroozi; Amir Abbas Shafiei; Abbas Haghighat; Gholam Reza Jahanshahi; Sayed Behrouz Mousavi (Wolters Kluwer Medknow Publications, 2012)
Background: Diabetes has become the next most widespread disease after cancer. Recent studies have found that diabetes and moderate to severe vitamin D deficiency are associated with reduced bone mineral content; therefore administration of vitamin D may correct these conditions. The purpose of this research is to compare the effect of vitamin D administration on bone to implant contact in diabetic rats with control group. Materials and Methods: In this randomized placebo-controlled trial, 48 Wistar rats were rendered diabetic (130≤ blood sugar ≤200 mg/dl) by IV injection of 35 mg/kg Alloxan. Implants were inserted in tibial bone; Then rats were divided into study and control groups and received oral vitamin D3 (160 IU) or placebo respectively for one week. Bone to implant contact value was measured under light microscope at 3 and 6 weeks. Results: Analysis of data indicated that vitamin D had no significant effect on bone to implant contact (BIC). At 3 weeks, the control group (n = 5) reported BIC level at 44 ± 19 and study group (n = 7) at 57 ± 20. At 6 weeks, the control group (n = 5) reported BIC level at 70 ± 29, and study group (n = 10) at 65 ± 22. Twenty one samples were missed because of death or incorrect lab processes. Conclusion: It seems that vitamin D supplement has no significant effect on BIC in 130 mg/dL ≤ blood sugar ≤200 mg/dL (P = 0.703) andwas also not time dependent (P = 0.074).